Selective THz control of magnetic order: new opportunities from superradiant undulator sources. (23rd February 2018) - Kovalev, S; Wang, Zhe; Deinert, J-C; Awari, N; Chen, M; Green, B; Germanskiy, S; de Oliveira, T V A G; Lee, J S; Deac, A; Turchinovich, D; Stojanovic, N; et al.
Abstract: Recent advancements of accelerator technology enable the generation of carrier-envelope-phase stable THz pulses with high fields at adjustable high repetition rates. The appropriate choice of THz radiator allows generation of narrow-band, spectrally dense, multicycle THz transients of tunable THz frequency which are ideally suited to selectively excite low-energy excitations such as magnons or phonons. They also allow one to study the frequency dependence of nonresonant THz-field interactions with various order parameters with high dynamic range. In this paper, we discuss the future prospects of this new type of THz light source for studying the coherent control of magnetic order based on recent results.